Substitutes or Complements? A Configurational Approach to Examining the Bundle of Governance Mechanisms - Misangyi, Vilmos F. (Institutional Knowledge at Singapore Management University, 2012)
Controlling the agency cost arising out of the separation of ownership from control, the central focus of agency theory, has guided the nearly thirty years of research on governance mechanisms. Yet, despite the recognition that the many governance mechanisms such as boards of directors, large shareholders, the market for corporate control, compensation contracts and equity holdings of managers among others operate as bundles together, our current understanding on how they operate as bundles is very limited. In this study, using qualitative comparative analysis to study the configurations of governance mechanisms in the context of S&P1500 firms, we demonstrate how governance mechanisms substitute for one another as well as act as complements. Furthermore, we highlight the contingent nature of such configurations in the context of firm size and environmental dynamism.